Photodynamic therapy for the prevention and treatment of actinic keratosis/squamous cell carcinoma in solid organ transplant recipients: a systematic review and meta‐analysis. (11th September 2019) - Liew, Y.C.C.; De Souza, N.N.A.; Sultana, R.G.; Oh, C.C.
Abstract: Solid organ transplant recipients (sOTR) are at an increased risk of developing cutaneous cancers, especially squamous cell carcinoma (SCC). Photodynamic therapy (PDT) for the prevention and treatment of actinic keratosis (AK)/SCC in sOTR is increasingly prescribed given the increase in solid organ transplantations performed worldwide. PDT has added advantages of superior cosmetic outcomes and good safety profile compared to conventional surgical methods and other topical therapies. We aim to evaluate the role of PDT in the prevention and treatment of AK/SCC in sOTRs. The Cochrane Library, PubMed and EMBASE database were searched. Articles reporting PDT outcomes amongst sOTR with or without AK/SCC at baseline were selected. We classified the studies into two categories: (i) PDT as prevention measure and (ii) treatment of AK/SCC in sOTR. Primary outcome for the prevention category was 3‐year incidence of AK/SCC and complete response (CR) of lesions after PDT exposure in the treatment category. Secondary outcomes were cosmesis and adverse reaction in both categories. Pooled results were expressed as risk difference (RD) with corresponding 95% confidence interval (95% CI). Twelve out of 641 articles met our eligibility criteria, out of which four RCTs reported the preventive effect of AK/SCC and another five RCTs reported the treatment effect of PDT in sOTR. One RCT did not report absolute number of lesions at baseline/end of study for results to be pooled in the quantitative analysis. The remaining three studies were cohort studies reporting treatment and preventive effect of PDT in sOTR. PDT group had a lower incidence as a preventive measure with pooled RD of 0.14 (95% CI 0.08–0.19). The CR in PDT was higher in the treatment group with a pooled RD of 0.77 (95% CI 0.6–0.94) and 0.50 (95% CI 0.22–0.79) in predivided lesional areas and number of lesions, respectively. In conclusion, PDT is efficacious for prevention and treatment of AK/SCC in sOTRs.